Health science research articles in American English and Brazilian Portuguese: a comparison study based on intercultural rhetoric - Oliveira Neto, José Belem de (2021)
Intercultural Rhetoric (IR) is the study of written discourse between individuals with different cultural backgrounds (CONNOR, 2011). To understand how rhetorical organization works in different genres (SWALES, 1990), for instance, research articles (RAs) in English and other languages can help to grasp the significance of understanding some of the challenges faced by authors from peripheral countries (KACHRU, 1996, MONTEIRO; HIRANO, 2020). In addition, this can help those who intend to publish in international journals (HIRANO, 2009). Although many studies have investigated and compared rhetorical organization of RAs in different disciplines and languages, few studies have compared the writing of medical RAs in American English and Brazilian Portuguese (HIRANO, 2009; REZENDE; HEMAIS, 2012; CONNOR; TRAVERSA, 2014; SAMRAJ; 2016). The present study analyzed the rhetorical organization of 20 research articles (RAs) Introduction-Methods-Results-Discussion-Conclusion - based on IR perspective. Of these RAs, 10 were written in American English and 10 were written in Brazilian Portuguese. The genre-analysis model proposed by Nwogu (1997) for medical RAs was used to the comparative analysis as starting point to identify rhetorical patterns in both languages. The major findings were the similarities and differences between both corpora related to rhetorical structure within difference sections of RAs, therefore, suggesting the existence of cross-cultural variation in academic writing between both languages. The results of the present study contribute with data related to rhetorical organization and linguistic features of RAs. This knowledge may help to improve awareness of writer and also may provide insights for language for academic purposes teachers in the writing classroom. The study briefly explores writing, publication, and pedagogical implications based on its findings